2021
DOI: 10.1001/jamanetworkopen.2021.12131
|View full text |Cite
|
Sign up to set email alerts
|

Global Incidence of Neurological Manifestations Among Patients Hospitalized With COVID-19—A Report for the GCS-NeuroCOVID Consortium and the ENERGY Consortium

Abstract: Key Points Question What are the incidence of and outcomes associated with neurologic manifestations in patients with COVID-19? Findings In this cohort study of 3744 patients in 2 large consortia, neurological manifestations were found in approximately 80% of patients hospitalized with COVID-19; the most common self-reported symptoms included headache (37%) and anosmia or ageusia (26%), whereas the most common neurological signs and/or syndromes were acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
248
3
24

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(293 citation statements)
references
References 50 publications
18
248
3
24
Order By: Relevance
“…The incidences of at least one new-onset neurological signs/symptoms in the context of COVID-19 infection were extremely wide-ranging, i.e., ~ 12 to ~ 85%. The wide extent of these percentages was based on retrospective and prospective studies from various countries: Austria (Zifko et al 2021); China (Mao et al 2020;Xiong et al 2020) Egypt (Khedr et al 2021); Iran (Amanat et al 2021;Ghaffari et al 2021); Italy (Benussi et al 2020;Rifino et al 2021;Travi et al 2021); France (Kremer et al 2020); Germany (Fleischer et al 2021); Mexico (Flores-Silva et al 2021); Pakistan (Iltaf et al 2020); Poland (Wnuk et al 2021); Portugal (Oliveira et al 2021); South Korea (Kim et al 2021);Spain (García-Azorín et al 2021a, b;García-Moncó et al 2020;García-Azorín et al 2021a, b;Romero-Sánchez et al 2020); Turkey (Karadaş et al 2020;Yuksel et al 2021); United States of America (Chachkhiani et al 2020;Eskandar et al 2021;Frontera et al 2021;Liotta et al 2020); multinational (Chou et al 2021). Systematic reviews with or without meta-analysis (Cagnazzo et al 2021;Chua et al 2020;Collantes et al 2021;Pinzon et al 2020;Romoli et al 2020;Tsai et al 2020;Vakili et al 2021) and narrative/ scoping reviews (Ahmed et al 2020;Maury et al 2021;Roy et al 2021...…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of at least one new-onset neurological signs/symptoms in the context of COVID-19 infection were extremely wide-ranging, i.e., ~ 12 to ~ 85%. The wide extent of these percentages was based on retrospective and prospective studies from various countries: Austria (Zifko et al 2021); China (Mao et al 2020;Xiong et al 2020) Egypt (Khedr et al 2021); Iran (Amanat et al 2021;Ghaffari et al 2021); Italy (Benussi et al 2020;Rifino et al 2021;Travi et al 2021); France (Kremer et al 2020); Germany (Fleischer et al 2021); Mexico (Flores-Silva et al 2021); Pakistan (Iltaf et al 2020); Poland (Wnuk et al 2021); Portugal (Oliveira et al 2021); South Korea (Kim et al 2021);Spain (García-Azorín et al 2021a, b;García-Moncó et al 2020;García-Azorín et al 2021a, b;Romero-Sánchez et al 2020); Turkey (Karadaş et al 2020;Yuksel et al 2021); United States of America (Chachkhiani et al 2020;Eskandar et al 2021;Frontera et al 2021;Liotta et al 2020); multinational (Chou et al 2021). Systematic reviews with or without meta-analysis (Cagnazzo et al 2021;Chua et al 2020;Collantes et al 2021;Pinzon et al 2020;Romoli et al 2020;Tsai et al 2020;Vakili et al 2021) and narrative/ scoping reviews (Ahmed et al 2020;Maury et al 2021;Roy et al 2021...…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a small cohort study reported that there was a 2.5 times higher incidence measure of COVID-19 in patients with MS compared to the general population [37]. A recent global cohort study (representing 13 countries and 4 continents) reported neurological symptoms, including headache and anosmia, in COVID-19 patients, and those patients with clinical neurological symptoms were more susceptible to in-hospital death [38]. In contrast, two independent studies reported that patients with MS are less likely to be susceptible to COVID-19 infection [39,40].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 6 , 9 Also, neurological symptoms have been reported in patients with COVID‐19. 11 , 14 , 42 Thus, it will be interesting to assess the long‐term effects of COVID‐19 in patients with mental diseases.…”
Section: Discussionmentioning
confidence: 99%